Hydrolysis of propyrisulfuron in water: Kinetics, influence of 34 environmental factors, transformation products identification, mechanisms and toxicities - Zemin Dong; Rendan Zhou; Wengen Wan; Han Li; Wenwen Zhou; Yichang He; Tianfang Xu; Guai Xie; Jun Xia; Jinjin Li; Long Wang; Xianluo Shi; et al. (Ecotoxicology and Environmental Safety, 2023)
Propyrisulfuron is a novel sulfonylurea herbicide used for controlling annual grass and broad-leaved weeds in fields, but its fates and behaviors in environment are still unknown, which are of utmost importance for environmental protection. To reduce its potential environmental risks in agricultural production, the hydrolysis kinetics, influence of 34 environmental factors including 12 microplastics (MPs), disposable face masks (DFMs) and its different parts, 6 fertilizers, 5 ions, 3 surfactants, a co-existed herbicide of florpyrauxifen-benzy, humic acid and biochar, and the effect of MPs and DFMs on its hydrolysis mechanisms were systematically investigated. The main hydrolysis products (HPs), possible mechanisms, toxicities and potential risks to aquatic organisms were studied. Propyrisulfuron hydrolysis was an acid catalytic pyrolysis, endothermic and spontaneous process driven by the reduction of activation enthalpy, and followed the first-order kinetics. All environmental factors can accelerate propyrisulfuron hydrolysis to varying degrees except humic acid, and different hydrolysis mechanisms occurred in the presence of MPs and DFMs. In addition, 10 possible HPs and 7 possible mechanisms were identified and proposed. ECOSAR prediction and ecotoxicity testing showed that acute toxicity of propyrisulfuron and its HPs for aquatic organisms were low, but may have high chronic toxicity and pose a potential threat to aquatic ecosystems. The investigations are significantly important for elucidating the environmental fates and behaviors of propyrisulfuron, assessing the risks in environmental protection, and further providing guidance for scientific application in agro-ecosystem.